Caracterização microestrutural da zona de transição de tubos de aço 9%Ni revestidos com superliga de níquel 625 com processo de soldagem GTAW-HW - Farias, Francisco Werley Cipriano (2019)
The 9%Ni steel was recently used for the first time on the field in the injection unit (IU) for the injection of CO2 into oil wells. Because such steels are operated in H2S medium and are susceptible to sulfide stress cracking, their pipes are cladded with Nibased superalloy 625 by using gas tungsten arc welding with a hot wire to prevent this phenomenon from occurring. The transition zone of substrate/clad can have high hardness and low toughness. In this work, this transition zone was analyzed through optical and scanning electron microscopy with energy dispersive X-ray spectrometry and electron backscatter diffraction, as well as Vickers microhardness, shear and bend tests. Metallographic analysis identified type I and II boundaries with distinct chemical gradients, MC-type carbides, Laves/γ eutectics, peninsulas macrosegregation, crystallographic texture close to <100> in the clads, residual strain, and drop of microhardness across the transition zone. The clads were approved in the shear and bend tests. This work proposes a new type II boundary formation mechanism in dissimilar welds of steels that do not exhibit the allotropic transformation δ → γ during the welding thermal cycle and changes in the solidification mode.